Assessing Midwifery and Medical Student’s Interprofessional Learning: the use of portfolio - Bulan Kakanita Hermasari; Ari Natalia Probandari; Zulaika Nur Afifah (Intelektual Pustaka Media Utama, 2018)
To evaluate the portfolio in assessing interprofessional learning between medical and midwifery students. The student portfolio is assessed using a rubric consisting of four assessment criteria. A total of 32 student portfolios were tested for reliability coefficients and interrater agreements. We conducted an in-depth interview with mentors and focus group discussion (FGD) with students for exploring their perceptions of the ability of the portfolio to assess the learning. Interview and FGD data were converted into verbatim transcripts then were analyzed by two coders using open coding techniques. The reliability coefficient is 0.808. Inter-rater agreements for each assessment criteria are ranging from moderate to high. Mentors and students have positive insights toward the assessment system. This study supports the use of portfolios as an interprofessional educational assessment tool.